2015
DOI: 10.1007/s10529-015-1847-8
|View full text |Cite
|
Sign up to set email alerts
|

Small intestinal injury in mice infected with respiratory influenza A virus: evidence for virus induced gastroenteritis

Abstract: Respiratory IAV infection, particularly infected by avian IAV, can cause small intestine structural damage and modify the local immune response, thereby resulting in gastroenteritis-like symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 11 publications
1
13
0
Order By: Relevance
“…At this time, we do not know if stromal cells and/or cells of myeloid lineage are involved in the protective effect. Zhang et al recently reported that, in addition to its profound effects on the lung, influenza infection affects mucosal epithelium in the intestinal tract 49 , consistent with our report of systemic inflammation induced by PR8 infection 16 and our results showing that administration of AT-1001 (larazotide acetate), an inhibitor of intestinal and lung leakage 28,31,32 , reduced PR8-induced mortality. Thus, it is possible that influenza-mediated intestinal leakage underlies changes in gut microbiota that are required for development of adaptive immunity 50 .…”
Section: Discussionsupporting
confidence: 92%
“…At this time, we do not know if stromal cells and/or cells of myeloid lineage are involved in the protective effect. Zhang et al recently reported that, in addition to its profound effects on the lung, influenza infection affects mucosal epithelium in the intestinal tract 49 , consistent with our report of systemic inflammation induced by PR8 infection 16 and our results showing that administration of AT-1001 (larazotide acetate), an inhibitor of intestinal and lung leakage 28,31,32 , reduced PR8-induced mortality. Thus, it is possible that influenza-mediated intestinal leakage underlies changes in gut microbiota that are required for development of adaptive immunity 50 .…”
Section: Discussionsupporting
confidence: 92%
“…As a respiratory disease, the liver injury does not typically occur during influenza A virus infection. That respiratory, gastrointestinal, and other mucosal tissues have experienced viral replication or immune damage, but do not influence non-mucosal organs, such as the liver or kidney [11][12][13]. However, some contradicting findings were obtained, such that a pandemic A ⁄ H1N1 (2009) influenza A virus, which is different from seasonal influenza, can lead to liver damage [14].…”
Section: Discussionmentioning
confidence: 99%
“…Fatality of the infection is related to pneumonia, which is characterized by massive lung inflammation resulting in damage of tissue [1] . It was demonstrated that influenza A virus (H1N1, H5N1 and H7N2) infection caused not only lung injury but also intestinal structural damage, thereby leading to gastroenteritis-like symptoms [2] . Clinically, gastrointestinal symptoms including abdominal pain, nausea, vomiting, and diarrhea often occur during influenza [3] .…”
Section: Introduction mentioning
confidence: 99%